TYPES OF POSITIVE COMMUNICATION IN THE PROBLEMATIC TEACHING OF PHYSICS IN SECONDARY SCHOOLS (Academicia Globe: Inderscience Research, 2022)
This article describes the types of communication, target communication, functional communication, and instrumental communication in accordance with their content in problem-based physics teaching in secondary school.